2018
DOI: 10.1371/journal.pone.0197692
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a mucosal gut microbial community in vitro using an artificial simulator

Abstract: The Twin Simulator of the Human Intestinal Microbial Ecosystem (TWINSHIME®) was initially developed to study the luminal gut microbiota of the ascending (AC), transverse (TC), and descending (DC) colon regions. Given the unique composition and potential importance of the mucosal microbiota for human health, the TWINSHIME was recently adapted to simulate the mucosal microbiota as well as the luminal community. It has been previously demonstrated that the luminal community in the TWINSHIME reaches a steady state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 48 publications
7
103
0
Order By: Relevance
“…13 Liu et al (2018) followed the development of their fecal community in the TWIN-SHIME by 16S rRNA and SCFA analyses. 17 In their study, the community structure became constant on day 10, whereas the communities' SCFA metabolism became constant not before day 17. Furthermore, in contrast to the complex fecal community, SIHUMIx develops simultaneously on the structural and metabolic level during adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…13 Liu et al (2018) followed the development of their fecal community in the TWIN-SHIME by 16S rRNA and SCFA analyses. 17 In their study, the community structure became constant on day 10, whereas the communities' SCFA metabolism became constant not before day 17. Furthermore, in contrast to the complex fecal community, SIHUMIx develops simultaneously on the structural and metabolic level during adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…The De-stat culture has not been applied for studies of complex microbial consortia earlier, while chemostat gut models have been used by several groups. It has been shown that major shifts in variability of fecal microbiota take place within the first 3–4 residential times while slight fluctuations occur even after 30 residential times [13,20,30] because of complex nature of the microbiota. Hence, the De-stat presented in the current paper is a promising approach for analyzing of the growth rate in microbial consortia with potential impact on health.…”
Section: Discussionmentioning
confidence: 99%
“…Before use, the samples were thawed at 37°C for 45 min in an anaerobic incubator and 250 µl of the sample was extracted using diethyl ether (1:2, v/v), 2‐methylhexanoic acid as the internal standard, sulfuric acid, and sodium chloride. The samples were well mixed and then centrifuged at 3,000 rpm (Centrisart A‐14C; Sartorious, Germany) to facilitate phase separation (Liu et al, ). The organic layer was transferred into a GC vial and 1 µl was injected into a gas chromatography/mass spectrometry (GC/MS) (Shimadzu QP2010 Ultra; Shimadzu, Columbia, MD), with a Stabilwax‐DA column, 30 m, 0.25 mm ID, 0.25 µm (Restek Corporation, Bellefonte, PA) with the following settings: injection port temperature set to 260°C, a split ratio of 1:20, a flow rate of 1.00 ml/min of helium.…”
Section: Methodsmentioning
confidence: 99%
“…The gut microbiota is a complex community of microorganisms found within the intestinal tract (Clayton et al, ; Daliri, Tango, Lee, & Oh, ; Lloyd‐Price, Abu‐Ali, & Huttenhower, ). The composition of the gut microbiota changes biogeographically, forming region specific communities adapted to each microenvironment (Liu et al, ). Within each region, the community will grow in the lumen, however, some of the community members will preferentially colonize the loose mucus layer lining the intestinal cells (Lavelle et al, ; Zhang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation